2003
DOI: 10.5194/acp-3-1301-2003
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic bromine in the marine boundary layer: a critical review

Abstract: Abstract. The cycling of inorganic bromine in the marine boundary layer (mbl) has received increased attention in recent years. Bromide, a constituent of sea water, is injected into the atmosphere in association with sea-salt aerosol by breaking waves on the ocean surface. Measurements reveal that supermicrometer sea-salt aerosol is substantially depleted in bromine (often exceeding 50%) relative to conservative tracers, whereas marine submicrometer aerosol is often enriched in bromine. Model calculations, lab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
268
4
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 265 publications
(295 citation statements)
references
References 176 publications
(168 reference statements)
15
268
4
1
Order By: Relevance
“…Debromination of sea-salt aerosol is not included in the model following the work of Schmidt et al (2016), which showed better agreement with observations of BrO made by the GOME-2 satellite (Theys et al, 2011) and in the free troposphere and the tropical eastern Pacific MBL (Gomez Martin et al, 2013;Volkamer et al, 2015;Wang et al, 2015). Emission rates and bromine chemistry included in the model are described in detail by Parella et al (2012), with the bromine chemistry scheme described by 19 bimolecular reactions, 2 threebody reactions and 2 heterogeneous reactions using rate coefficients, heterogeneous reaction coefficients and photolysis cross sections recommended by Sander et al (2011).…”
Section: Global Modelmentioning
confidence: 83%
See 2 more Smart Citations
“…Debromination of sea-salt aerosol is not included in the model following the work of Schmidt et al (2016), which showed better agreement with observations of BrO made by the GOME-2 satellite (Theys et al, 2011) and in the free troposphere and the tropical eastern Pacific MBL (Gomez Martin et al, 2013;Volkamer et al, 2015;Wang et al, 2015). Emission rates and bromine chemistry included in the model are described in detail by Parella et al (2012), with the bromine chemistry scheme described by 19 bimolecular reactions, 2 threebody reactions and 2 heterogeneous reactions using rate coefficients, heterogeneous reaction coefficients and photolysis cross sections recommended by Sander et al (2011).…”
Section: Global Modelmentioning
confidence: 83%
“…Emissions of inorganic iodine species (HOI and I 2 ) use the results of Carpenter et al (2013), with oceanic iodide concentrations parameterised by MacDonald et al (2014). The iodine chemistry scheme includes 26 unimolecular and bimolecular reactions, 3 three-body reactions, 21 photolysis reactions and 7 heterogeneous reactions, using recommendations by Atkinson et al (2007) and Sander et al (2011) where available. Full details are given by Sherwen et al (2016a, b).…”
Section: Global Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The main known sources of reactive bromine and iodine species to the troposphere are emissions of organic halocarbons from macroalgae [65] and sea salt aerosol which provides the largest source of bromine [66]. There is also some evidence that the rainforest might provide a small natural source.…”
Section: Role Of Halogen Speciesmentioning
confidence: 99%
“…Bromine is a minor constituent in the Earth's atmosphere, but it plays an important role in atmospheric chemistry due to its ozone depletion capabilities [5,15]. Like iodine, oceans are the main natural reservoir of Br with average concentrations about 65 mg L −1 [16].…”
mentioning
confidence: 99%